Painting of the Renaissance - Wundram, Manfred 1925-2015 (Epochs & styles, 1997)
Focuses on European painting of the 15th and 16th centuries and examines works by Altdorfer, Bellini, Bosch, Botticelli, Brueghel, Carpaccio, Correggio, Cranach, Dürer, van Eyck, Giorgione, El Greco, Grünewald, Holbein, Leonardo da Vinci, Mantegna, Masaccio, Michelangelo, Piero della Francesca, Raphael, Tintoretto, Titian, Uccello, Veronese, van der Weyden, and more. Includes brief biographies of the artists